Abdominoperineal posterior sagittal anorectoplasty without protective colostomy in high arm pouch colon surgery - Sasanka Nath; Subhashis Karmakar; Samput Mallick (Asian Journal of Medical Sciences, 2023)
Background: In high anorectal malformations (ARM), surgical management includes initial colostomy at neonatal period followed by abdominoperineal posterior sagittal anorectoplasty (PSARP) without a protective colostomy. Aims and Objectives: The aims of this study were as follows: (i) To evaluate whether 2 stage PSARP gives better outcome for high ARM than three stage and (ii) to assess overall stay duration, cost incurred, and complications associated with two stage PSARP. Materials and Methods: A total 30 patients were studied. Fifteen patients with classical abdominoperineal PSARP with protective colostomy (three stages) constituting Group A studied retrospectively and 15 patients were studied in Group B who underwent neonatal colostomy followed by abdominoperineal PSARP without protective colostomy (Two stages). Comparative study was done between the two groups for a better choice of procedure in high ARM patients. Results: In Group A, blood transfusion required was more than Group B. Mean expense incurred in Group A was more than Group B. Complications in Group A occur in eight patients, whereas in Group B, complications occurred in six patients. Conclusion: Stages of high ARM and pouch colon are better alternative to three stages repair in all aspect.